Examining Tourist Visit Intention to Nature-Based Tourism in Post-COVID-19 Pandemic - Kusdibyo, Lusianus; Budhi Septyandi, Chandra; Kania, Rafiati (KnE Social Sciences, 2023)
The study aims to investigate tourist visit intentions to nature-based tourism destinations after the COVID-19 pandemic. The theory of planned behavior (TPB) was used as the primary theoretical foundation to foresee tourist visit intention. This study used a quantitative research design with a purposive sampling technique to collect data. A total of 325 datasets were found to be suitable for the next analysis using partial least square structural equation modeling (PLS-SEM). The findings indicate that entirely of the TPB factors are significant in influencing tourist visit intention. Specifically, tourist attitude has the greatest influence on tourist visit intention. It implies that the TPB can effectively forecast tourist visit intention to nature-based tourism destinations. Consequently, destination managers should consider the TPB elements when making decisions. Keywords: nature-based tourism, theory planned behavior, visit intentions, post- COVID-19, PLS-SEM